Anaplasma phagocytophilum AFAP targets the host nucleolus and inhibits induced apoptosis - Zhang, Daxiu; Yu, Lifeng; Tang, Hui; Niu, Hua (Frontiers in Microbiology, 2025)
Anaplasma phagocytophilum, the etiologic agent of human granulocytic anaplasmosis (HGA), is an obligate intracellular Gram-negative bacterium. During infection, A. phagocytophilum transfers its type IV secretion system (T4SS) effector proteins into host cells to manipulate cellular processes. AFAP (an actin filament-associated Anaplasma phagocytophilum protein) was identified as a T4SS effector protein and found to interact with the host nucleolin, as described in a previous study. In this study, proteomic analysis was performed to extensively identify AFAP-interacting proteins in host cells and analyze the potential role of AFAP in modulating host cellular processes. A total of 586 host proteins were identified interacting with AFAP by data-independent acquisition mass spectrometry and annotated to 501 Gene Ontology (GO) terms, with the significantly over-represented ones related to ribosomes, nucleolus, DNA binding, and rRNA metabolic process. Given the role of the nucleolus in cellular stress response, the targeting of AFAP to the nucleolus, and the identification of dozens of AFAP-interacting proteins that were annotated to the GO term (GO:0072331, signal transduction by p53 class mediator), the role of AFAP in modulating host apoptosis was determined. AFAP was found capable of inhibiting induced apoptosis. Thus, the proteomic analysis of AFAP-interacting proteins and determination of AFAP with anti-apoptotic activity may help elucidate the role of this T4SS effector protein in HGA pathogenesis.